The effect of skills training in the development of equilibrium motor of motoral Lag Children. - بن ميصرة عبد الرحمان; بركات حمزة; زروق نايل (sports creativity, 2025)
The importance of studying the motor skill component parts through means of motor training provides imfrtant information for workers in the field of sports at Various levels in order to dscribe the improving performance . To do that, the researchers used the empirical research method on two , an expérimental group and a control group both inctuded 12 children whom are the study sample. The mathematical averages and the tests. The results of this study have shown us that there is a signiticant to the improvement in the motor skills of these student thanks motor training however there are some significant differences between the two groups cancerning the variables in favor of the expérimente group. It is recommended to use these suggested trining for this age of all kindergarten children.